Comprehensive metabolite profiling and evaluation of anti-nociceptive and anti-inflammatory potencies of Nypa fruticans (Wurmb.) leaves: Experimental and in-silico approaches - Farhana Islam; Md. Aktaruzzaman; Md. Tarikul Islam; Fariya Islam Rodru; Saquiba Yesmine (Heliyon)
Globally, inflammation and pain are among the most prevalent health issues. The use of medicinal plants to alleviate these conditions is growing. This study comprehensively investigated the analgesic and anti-inflammatory properties of the ethyl-acetate extract of Nypa fruticans (EENF) leaves, traditionally used in folk Medicine. High-performance liquid chromatography (HPLC) and gas chromatography-mass spectroscopy (GC-MS) were employed to identify the phytochemicals in EENF. In vitro antioxidant studies were conducted to determine the antioxidative properties of EENF. Formalin-induced paw edema assay was employed to assess the in-vivo anti-inflammatory activity whereas; acetic acid-induced writhing test, hot plate test, and tail immersion test were performed to evaluate the in vivo anti-nociceptive effects. The identified compounds were subsequently evaluated by computational studies against the cyclooxygenase-2 enzyme. EENF demonstrated significant antioxidant activity in both the DPPH scavenging assay (IC50: 105.18 μg/mL) and the reducing power assay (RC50:1752.76 μg/mL). In the in-vivo anti-inflammatory assay, EENF exhibited the highest (50.39 % and 67.72 %) inhibition of edema at the fourth hour at 200 and 400 mg/kg body weight, accordingly. Moreover, all the pain modulation studies demonstrated significant (p < 0.001) analgesic properties of EENF in a dose-dependent manner. Among, the 23 identified phytocompounds, the most promising ones were determined to be potential anti-nociceptive and anti-inflammatory agents through molecular docking studies and ADME/T analysis. Molecular dynamics simulations (MDS) confirmed the stability of the protein-ligand complexes. Two phytochemicals, (−) Epicatechin (CID 72276) and Quercetin (CID 5280343), outperformed the standard anti-inflammatory drug, diclofenac sodium, in MDS studies. Both experimental and in-silico studies have scientifically verified the traditional use of Nypa fruticans in treating pain and inflammatory disease. Overall, (−) Epicatechin and Quercetin possess excellent potential as natural lead compounds for COX-2 inhibition. Further research, including pure compound isolation and biomolecular studies, is needed to understand the underlying mechanisms of these activities.